Procedimentos terapêuticos ocupacionais em instituições de longa permanência para idosos: uma revisão sistemática da literatura - MEDEIROS, Bianca Casseb (2023)
Seniors residing in a Longterm care require interventional actions for their welfare. Studies highlight that the context within a LPI is still loaded by negative events that lead to the institutionalized elderly loss of functional and cognitive ability. However, it is noteworthy positive situations, such as: security and reception. In this context, the motivation for proposing this study came after some questions about what kind of measures that may be taken by professional and occupational therapy students who work with this clientele. Thus the literature of conduct and / or procedures in place for occupational therapists in order to sort the main interventions with institutionalized elderly, since there are few studies and some gaps on the subject, in particular related to our regional context (State For). It aims to promote a literature review of the literature on interventions, procedures and / or conduct of occupational therapy with elderly people living in longstay institutions. It conducted a bibliographic retrospective and secondary survey content published in indexed and available magazines scientific search sites: Bireme, LILACS, MEDLINE and PubMed, including articles published in the last 10 years, using the following descriptors: “Geriatrics” and "Occupational Therapy ", “Longterm care” and “Occupational Therapy”, “Institutionalized and “Occupational Therapy”; “Nursing Home”, and “Occupational Therapy" and "Older" and "Occupational Therapy". We selected 11 studies that met the preestablished inclusion criteria, these were categorized and analyzed for the level of evidence with use of the PEDro scale. The studies showed effective procedures ranging from stabilization of cognitive behavioral skills, physical and functional to improving the quality of life in institutionalized elderly. However, the level of evidence analysis showed low or moderate scores of much of these studies. Conclusion: from the critical analysis of occupational therapy procedures can infer their applicability in the institutional context. A systematic review of the literature on the procedures of Occupational Therapy with institutionalized elderly may support practices in this context, as well as instigating professionals to reflect and propose new research in the area more specifically. This study failed to close all gaps questioned, but presents with originality to propose an initiative procedures that poderm depth in the Brazilian regional context and meeting the local needs and the public attention, requiring further studies.